Power of Bode Index in Predicting Future Exacerbations of COPD - A Prospective Observational Study - Fakruddin, Dr Mohammad; Y, Dr Shivalinga; Abbas, Dr Mohammad (International Journal of Innovative Research in Medical Science, 2025)
Background and Objective: The prevalence and the burden of COPD are projected to increase in the upcoming decades due to the continued exposure to COPD risk factors and changing age structure of world’s population. BODE index is a multidimensional grading system for COPD assessment which combines 4 variables and is a simple and excellent predictor of survival and mortality in COPD patients. Objectives of the study are: 1. To predict prognosis and future risk of exacerbations in COPD patients on first visit on the basis of BODE index. 2. To assess the accuracy of prediction using BODE index during the follow up visits. Materials and methods: A prospective clinical study was conducted among 40 stable COPD patients who attended or got admitted at Mandya Institute of Medical Sciences during a time period of 12 months. Spirometry is done at the time of admission. Further, the patients were observed for future exacerbations of COPD by following up of cases once in 30 days for a period of 6 months. Results: In the study, the mean age of the participants was 60 years with the standard deviation of around ±3.737 years. Majority were males and more than one third of the study participants i.e., around 35.0% had given history of presence of co-morbidities. The mean value of BODE Index obtained was 3.50 with the standard deviations of around ±21.95. Majority of the participants i.e., about 80.0% of them belonged to the Stage 2 based on GOLD Staging. The next common stage was Stage 3 followed by Stage 1. The study found statistical and positive correlation of exacerbations in COPD with both BODE Index and GOLD Staging, after 6 months. Also the exacerbations of COPD was observed each month among the participants, accordingly, only 4-6 cases had experienced exacerbations in each month, while majority of participants were feeling better. At the end of 6 months, on estimating the total number of exacerbations of COPD, majority i.e., around 47.5% of the participants had no exacerbations overall. Conclusion: The study found that BODE Index on first visit was successful in foreseeing the prognosis of the condition of the patient. Also it accurately predicted the future risk of exacerbations as it was positively correlated with the number of exacerbations in the follow up period. Even the correlation of the severity of the condition with the GOLD staging was established.